A case of angioid streaks that produced choroidal neovascularization after the onset of unilateral acute retinopathy in pseudoxanthoma elasticum - Akika Kyo; Manabu Yamamoto; Shigeru Honda (American Journal of Ophthalmology Case Reports, 2022)
Purpose: To report a case of angioid streaks that showed non-exudative choroidal neovascularization (CNV) after the onset of acute retinopathy in pseudoxanthoma elasticum (PXE). Observations: A 64-year-old woman with PXE visited our department for an ophthalmologic evaluation. Her decimal best-corrected visual acuity (BCVA) was 1.5, with angioid streaks (AS) around the optic disc in either eye at the first visit. Seven years later, her left eye's BCVA suddenly decreased by 0.3, and the fundus showed blurring of the Ellipsoid zone and vitreous cells along with the retinal pigment streaks on the nasal fovea. Diagnosed as acute retinopathy in PXE, twenty-two weeks after the start of oral prednisolone, the Ellipsoid zone became clear and the BCVA improved to 1.2, but CNV gradually developed. After intravitreal injection of bevacizumab, the CNV was decreased. Conclusions and importance: CNV on the AS lesion may occur after acute retinopathy in PXE.